BIOLOGIA DE ð˜—ð˜ð˜°ð˜¥ð˜ªð˜¢ ð˜ªð˜¯ð˜µð˜¦ð˜³ð˜±ð˜¶ð˜¯ð˜¤ð˜µð˜¦ð˜ð˜ð˜¢ (HÃœBNER, 1813) (LEPIDOPTERA, PYRALIDAE) EM DIETA ARTIFICIAL - Amaral FÂº, B. F.; Habib, M. E. M. (REVISTA DE AGRICULTURA, 2020)
BIOLOGIA DE ð˜—ð˜ð˜°ð˜¥ð˜ªð˜¢ ð˜ªð˜¯ð˜µð˜¦ð˜³ð˜±ð˜¶ð˜¯ð˜¤ð˜µð˜¦ð˜ð˜ð˜¢ (HÃœBNER, 1813) (LEPIDOPTERA, PYRALIDAE) EM DIETA ARTIFICIAL